Zeaxanthin and Lutein: Photoprotectors, Anti-Inflammatories, and Brain Food - Barbara Demmig-Adams; Marina López-Pozo; Jared J. Stewart; William W. Adams (Molecules, 2020)
This review compares and contrasts the role of carotenoids across the taxa of life—with a focus on the xanthophyll zeaxanthin (and its structural isomer lutein) in plants and humans. Xanthophylls’ multiple protective roles are summarized, with attention to the similarities and differences in the roles of zeaxanthin and lutein in plants versus animals, as well as the role of meso-zeaxanthin in humans. Detail is provided on the unique control of zeaxanthin function in photosynthesis, that results in its limited availability in leafy vegetables and the human diet. The question of an optimal dietary antioxidant supply is evaluated in the context of the dual roles of both oxidants and antioxidants, in all vital functions of living organisms, and the profound impact of individual and environmental context.